2021
DOI: 10.1007/s10530-021-02576-7
|View full text |Cite
|
Sign up to set email alerts
|

Matching a snail’s pace: successful use of environmental DNA techniques to detect early stages of invasion by the destructive New Zealand mud snail

Abstract: Early detection of invasive species allows for a more rapid and effective response. Restoration of the native ecosystem after an invasive population has established is expensive and difficult but more likely to succeed when invasions are detected early in the invasion process. Containment efforts to prevent the spread of known invasions also benefit from earlier knowledge of invaded sites. Environmental DNA (eDNA) techniques have emerged as a tool that can identify invasive species at a distinctly earlier time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 72 publications
(122 reference statements)
1
7
0
Order By: Relevance
“…Additional detections with eDNA sampling on this landscape were consistent with eDNA transport from a nearby, hydrologically connected site with known historical species occurrence. Further, the performance of Pyrgulopsis eDNA sampling here is consistent with the literature on morphologically similar invasive hydrobiid New Zealand Mudsnails ( Potamopyrgus antipodarum ) (Goldberg et al., 2013; Ponce et al., 2021; Woodell et al., 2021). Multiple studies have found that eDNA sampling for P. antipodarum can be effective, even for low density population detection.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Additional detections with eDNA sampling on this landscape were consistent with eDNA transport from a nearby, hydrologically connected site with known historical species occurrence. Further, the performance of Pyrgulopsis eDNA sampling here is consistent with the literature on morphologically similar invasive hydrobiid New Zealand Mudsnails ( Potamopyrgus antipodarum ) (Goldberg et al., 2013; Ponce et al., 2021; Woodell et al., 2021). Multiple studies have found that eDNA sampling for P. antipodarum can be effective, even for low density population detection.…”
Section: Discussionsupporting
confidence: 87%
“…(2021) reported concordance in eDNA sampling and conventional kick‐net sampling for P. antipodarum across six streams in Washington (USA) and Woodell et al. (2021) reported detection of a new invasion with eDNA sampling in Pennsylvania (USA), which was later confirmed with conventional sampling.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These results have the potential for application to control of invasive populations of P. antipodarum, and especially populations earlier in the invasion process (e.g. Woodell et al (2021)). These outcomes also suggest value in addressing a role for density dependence in population dynamics of other invasive freshwater taxa.…”
Section: Discussionmentioning
confidence: 94%
“…(Hulme, 2006;Davis, 2009). Early detection, diagnosis, and monitoring of invasive species are particularly important because of the benefits for rapid and effective response and the formulation of corresponding prevention and control decisions to curb the spread and expansion of invasive species (Hulme, 2006;Woodell et al, 2021).…”
Section: Introductionmentioning
confidence: 99%